Pengembangan Media Pobosita (Pop Up Book Sistem Tata Surya) Pada Mata Pelajaran IPA Kelas VI MI YKUI Sambogunung - Diah Eka Nurlaeli Agustin; Nataria Wahyuning Subayani (Jurnal Kajian dan Penelitian Umum, 2024)
This study aims to produce positive learning media, identify the feasibility of positive learning media through validity, effectiveness and response. This research is research and development, using the ADDIE model through five stages, namely analysis, design, development, implementation, and evaluation. This possita media is validated by media experts and material experts. Pobosita media was tested in class VI MI YKUI Sambogunung with 1 trial. After conducting the trial, there is a student response questionnaire filling out and a student learning achievement test to determine the effectiveness of the media posita. The results of the media expert 1 validation test obtained a score of 91.67%, the media expert 2 obtained a score of 95%, the material expert 1 obtained a score of 100%, and the validation of the material expert 2 obtained a score of 96.4% with a very valid category. While the learning outcomes test obtained a score of 90% in the complete category and the results of filling out the student response questionnaire obtained a score of 83.4% in the very good category. Possible media can be said to be feasible after media validation and can be said to be effective after conducting trials.